Solidificação e estabilização do lodo galvânico em cimentos supersulfatados - Camargo, Guilherme Holub (2018)
Galvanic sludge is a waste from the electroplating industry considered dangerous due to the presence of heavy metals in its constitution, its disposal and treatment must be carried out following technical norms and regulated by environmental legislation. Its treatment is very costly for the industries and its application in some engineering process becomes more and more feasible. The technique of solidification and stabilization, are presented as an alternative for the treatment of this type of material, using a cement as a binder. The supersulfated cement is known to be a binder of low environmental impact due to the materials that compose it. The main constituents of supersulfated cement are: blast furnace slag (up to 90%), calcium sulfate (10-20%) and a small amount of alkaline activator (up to 5%). Studies highlight the formation of the ettringite phase during the hydration of this material and this phase is associated to the retention of heavy metals. This research deals with the addition of galvanic sludge in supersulfated cement, in two proportions, in the form of pulps cast in cylindrical molds 2 cm x 4 cm, in order to report the effects on the mechanical properties and microstructures, besides leaching test to evaluate the retention of chromium. The compressive strengths in the samples evaluated presented interesting mechanical properties, and the proportion of the CSS 80 20 and CSS 80 20 + LG pulp had the best results at 7 days, 19.1 and 14.9 MPa respectively, and 28 days, 26.3 and 24.2 MPa respectively. The microstructural analysis evidenced the formation of the hydrated phases and the encapsulation of the chromium metal in the ettringite phase was observed by the application of the SEM-EDS. The leaching tests presented results within the limits established by the legislation.